The antinociceptive effect of electroacupuncture at different depths of acupoints and under the needling surface - Silva Marcelo L; Silva Josie RT; Prado Wiliam A (BMC, 2012)
Abstract Background The stimulation of acupoints along the meridians, but not the non-acupoints outside of the meridians, produces analgesia. Although the acupoint is defined at the body surface, the exact location of the acupoints is not known. This study aims to examine whether the intensity and duration of the analgesic effect of electroacupuncture (EA) at the Zusanli (ST36) and Sanynjiao acupoints (SP6) change according to the depth of the stimulation. Methods Ninety-six male Wistar rats classified as responders were arbitrarily allocated into 16 groups of six rats each. Six groups received EA with uninsulated acupuncture needles (type I) or needles that were immersed in varnish and had the varnish circularly peeled 0.2 mm from the tip (type II), 0.2 mm at 3 mm (type III) or 5 mm (type IV) from the tip, or 0.2 mm at 5 and 1 mm from the tip (type V), or EA sham for 20 min. Five groups received injection of formalin into the acupoint bilaterally at 5 mm or 1 mm deep into ST36, 5 mm below ST36 but inserting the needle at 45° to the skin surface, or 5 mm deep into non-acupoints. The remaining groups received intraplantar injection of saline, 1% or 2.5% formalin. The analgesic effects were measured by the rat tail-flick test. Results The bilateral stimulation of ST36 and SP6 by uninsulated or insulated needles produced analgesia in the rat tail-flick test. The stronger and longer lasting effects occurred after EA with the types I and V needles, or injection of formalin 5 mm deep into ST36. The remaining needles produced weaker and shorter lasting effects. Slow analgesic effect also occurred after formalin injection at 1 mm or 5 mm below ST36 by inserting the needle at 45° to the skin surface. Conclusion The experimental results suggest that the efficacy of the EA stimulation depends on the spatial distribution of the current density under the needling surface rather than only the acupoint or the depth of needling.